A multi-objective model for optimal operation of a battery/PV/fuel cell/grid hybrid energy system using weighted sum technique and fuzzy satisfying approach considering responsible load management. (1st March 2017) - Majidi, Majid; Nojavan, Sayyad; Nourani Esfetanaj, Naser; Najafi-Ghalelou, Afshin; Zare, Kazem
Highlights: Multi-objective model is proposed to minimize operation cost and CO2 emission. Weighted sum technique is used to solve the proposed multi-objective model. A set of Pareto solutions is achieved based on different weighted coefficients. Fuzzy satisfying approach is used to select the trade-off solution. Demand response program is used to reduce operation cost and CO2 emission. Abstract: In the past, no attention was paid to the kinds of sources by which loads were supplied and the only energy resource supplying electrical demand was the upstream grid. Recently, due to the appearance of new technologies in the field of energy resources such as distributed generation systems, operators are encouraged to use these resources along with upstream grid to ensure a reliable power to the load and reduce the role of upstream grid in supplying electrical demand. In the proposed paper, several renewable and non-renewable energy sources like photovoltaic system (PV), fuel cell (FC) and battery storage are integrated in a grid-connected hybrid energy system to supply energy demand. In this paper, a multi-objective optimization model is proposed to solve the cost-emission problem of battery/PV/fuel cell hybrid system in the presence of demand response program (DRP). Two conflicting objective functions namely minimization of total cost of hybrid system and reduction of CO2 emission are the main goal of proposed multi-objective model. The proposed model is solved by weighted sum technique and the best possible solution is selected by employing fuzzy satisfying approach. DRP transfers some amount of load from peak periods to other periods which flattens the load curve and minimizes total cost of system. A mixed-integer linear program is used to model the proposed cost-emission operation problem of hybrid system and it is solved by GAMS software. Two different cases have been studied to show the effects of DRP and the results are compared.